Is the Cytosolic Pi Concentration a Limiting Factor for Plant Cell Respiration? - Rebeille, Fabrice (1984)
The substrate-dependent O(2) uptake by sycamore (Acer pseudoplatanus L.) cell mitochondria in the presence of ADP and limiting Pi concentrations has been measured. The Pi concentration for half-maximum O(2) uptake rate was found to be in the range 20 to 50 micromolar for all the substrates tested. (31)P NMR of intact sycamore cells indicated that the Pi concentration in the cytoplasm was in the range 5 to 6 millimolar, approximately 100-fold higher than the Pi concentration required for maximum O(2) uptake rates by isolated mitochondria. When sycamore cells were transferred to a culture medium devoid of Pi, the cytoplasmic Pi concentration decreased from 6 to less than 3 millimolar, but the intact cell respiration remained practically constant for at least 4 days. These results strongly suggest that, in vivo, the respiration rate of sycamore cells is not limited by the quantity of Pi supplied to the mitochondria.